Jump landings in snowboarding: an observational study - McAlpine, P.; Kurpiers, N.; Kersting, U. (Science and Skiing IV, 2008)
INTRODUCTION: There is only one observational study published on falling in the sport of snowboarding (Cooper & Greenwald, 2005). This work concluded that terrain park facilities in mountain areas are associated with an increased risk of falling. Further investigation of landing and falling body movements within such areas of ski resorts is therefore warranted.